Famotidine Improved Schizophrenia-Like Behaviors in Acute Ketamine Model of Schizophrenia in Rats - (:unkn) unknown (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2020)
Objective: Schizophrenia is a devastating disorder with its positive (hallucination and delusion), negative (such as social withdrawal, anhedonia), and cognitive (learning and attention deficits) symptoms. Although current antipsychotic drugs treat positive symptoms, negative and cognitive symptoms have remained untreated. There is a limited number of studies showing the promising potential benefits of famotidine, an H2 receptor antagonist used for the treatment of peptic ulcer, in schizophrenic patients. In our previous study, it was showed that famotidine might improve schizophrenia-induced molecular deficits on Akt/GSK-3 beta/beta-Catenin signaling pathway in SH-SY5Y cells and there is no translational study examining this effects of famotidine. Hence this study was designed to investigate the effects of famotidine on schizophrenia-like behavioral deficits in the acute ketamine model of schizophrenia in rats. Methods: Male Sprague Dawley rats divided into the four groups as saline, famotidine, ketamine, ketamine+famotidine (n=8 per group). Prepulse inhibition (PPI) of acustic startle response, novel object recognition (NOR), fear conditioning (FC), and social interaction (SI) tests were performed to measure schizophrenia-like symptoms in rats. Ketamine (10 mg/kg) was administered 15 min before the PPI test or 15 mg/kg 30 min before the NOR, FC, and SI tests whereas famotidine (4.4 mg/kg) was administered 30 min before all behavioral tests. Results: Ketamine decreased the PPI (%) at +8 dB (p<0.01) and +16 dB (p<0.001) prepulse intensities compared to saline and famotidine treated group had higher (p<0.05) PPI (%) at +16dB prepulse intensity compared to ketamine. In NOR test, ketamine injected rats did not cause an increase in time spent with novel objects compared to familiar ones. In contrast, saline and famotidine pretreated rats spent more (p<0.05 and p<0.01) time with a novel object than a familiar one. In FC, ketamine decreased the freezing time (p<0.05) compared to saline, while famotidine pretreatment found to be ineffective. In SI, ketamine caused a decrease in sniffing and total interaction compared to control, while famotidine pretreatment increased (p<0.05) the sniffing behavior compared to the ketamine group. Conclusion: Our results indicated that beneficial effect of famotidine in previous clinical studies was confirmed in animal model of schizophrenia in rats, and suggested translational value of this study for potential antipsychotic effects of famotidine.
Keywords: Ketamine; Famotidine; Schizophrenia; Prepulse Inhibition; Novel Object Recognition; NMDA RECEPTOR ANTAGONISTS; NEGATIVE SYMPTOMS; COGNITIVE DYSFUNCTION; PREPULSE INHIBITION; CLINICAL-TRIAL; STARTLE; FEAR; PHENCYCLIDINE; HIPPOCAMPUS; PSYCHOSIS